Lithium battery positive electrode slurry as well as homogenizing method and application thereof

A composite conductive agent-based homogenization method for LMFP and NCM creates a multi-dimensional network, addressing conductivity and stability issues, enhancing lithium battery performance.

CN119230754APending Publication Date: 2024-12-31ZHEJIANG LEAPENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411507317.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Conventional blending methods for lithium manganese iron phosphate (LMFP) and ternary nickel cobalt manganese oxide (NCM) in lithium batteries result in poor slurry stability, low conductivity, and increased internal resistance due to differences in particle size and specific surface area, leading to poor electrochemical performance.

Method used

A homogenization method involving a composite conductive agent comprising granular, fibrous, and flaky conductive agents, along with a dispersant, is used to create a multi-dimensional conductive network, improving particle dispersion and conductivity in the slurry.

Benefits of technology

The method enhances the stability and conductivity of the positive electrode slurry, reducing internal resistance and improving rate and cycle performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230754A_ABST
    Figure CN119230754A_ABST
Patent Text Reader

Abstract

The invention relates to lithium battery positive electrode slurry and a slurry homogenizing method and application thereof. The homogenizing method comprises the following steps that a composite conductive agent, a dispersing agent and a polyvinylidene fluoride glue solution are mixed to obtain conductive slurry, the composite conductive agent comprises a first granular conductive agent and a fibrous conductive agent, and the mass ratio of the first granular conductive agent to the fibrous conductive agent is 1: 4-15: 1; mixing the conductive slurry with lithium manganese iron phosphate to obtain premixed slurry; mixing ternary nickel cobalt lithium manganate with a second granular conductive agent to obtain premixed powder; and mixing the premixed slurry with the premixed powder to obtain mixed slurry, adjusting the viscosity of the mixed slurry, and performing vacuum pumping and sieving to obtain the lithium battery positive electrode slurry. The homogenization method provided by the invention effectively constructs a multi-dimensional conductive network, improves the stability of the positive electrode slurry, further improves the conductivity of the prepared lithium battery, reduces the internal resistance of the battery, improves the rate capability and cycle performance, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium battery positive electrode slurry and a homogenization method and application thereof. Background Art

[0002] With the continuous development of lithium battery technology, higher requirements are put forward for the capacity, voltage, service life, safety and cost of lithium batteries. At present, the industry uses a mixture of lithium manganese iron phosphate (LMFP) and ternary nickel cobalt manganese oxide (NCM) materials to meet the requirements of high safety, high capacity, long battery life, long service life and low cost of lithium batteries.

[0003] However, when the conventional blending method is used for homogenization, due to the large differences in particle size and specific surface area of ​​LMFP and NCM, when the LMFP and NCM dry powders are directly blended, the small particles of LMFP are easily adsorbed on the surface of the large particles of NCM, resulting in the loss of the conductive network on the surface of the NCM, poor slurry stability, low compaction density, and poor conductivity of the obtained pole piece, which in turn makes the lithium battery polarization large, the cycle performance poor, and the DC internal resistance (DCR) increase rapidly. In particular, when the blending ratio of small particles of LMFP reaches more than 30%, the impact on the electrical performance of the lithium battery is more serious; in addition, when LMFP and NCM are separately made into positive electrode slurry and then coated in a mixed manner to prepare the electrode, since LMFP and NCM are evenly distributed in the electrode, the two materials have conductive paths of different lengths during charging and discharging, resulting in low current uniformity, and more contact interfaces will be formed between the two materials, thereby increasing the battery impedance.

[0004] Therefore, there is an urgent need for a positive electrode slurry homogenization method that can improve the particle dispersion uniformity and conductivity in the mixed slurry of LMFP and NCM, thereby improving the electrochemical performance of lithium batteries. Summary of the invention

[0005] Based on this, it is necessary to provide a lithium battery positive electrode slurry and a homogenization method and application thereof to address the above problems. The homogenization method provided by the present invention effectively constructs a multi-dimensional conductive network, improves the stability of the positive electrode slurry, thereby improving the conductivity of the prepared lithium battery, reducing the internal resistance of the battery, and improving the rate performance and cycle performance, and has broad application prospects.

[0006] A method for homogenizing a lithium battery positive electrode slurry comprises the following steps:

[0007] Mixing a composite conductive agent, a dispersant and a polyvinylidene fluoride glue to obtain a conductive slurry, wherein the composite conductive agent includes a first granular conductive agent and a fibrous conductive agent, and the mass ratio of the first granular conductive agent to the fibrous conductive agent is 1:4 to 15:1;

[0008] Mixing the conductive slurry with lithium iron manganese phosphate to obtain a premixed slurry;

[0009] Mixing ternary nickel-cobalt-manganese lithium oxide with a second granular conductive agent to obtain a premixed powder;

[0010] The premixed slurry is mixed with the premixed powder to obtain a mixed slurry. After the viscosity of the mixed slurry is adjusted, vacuuming and sieving are performed to obtain a positive electrode slurry for a lithium battery.

[0011] In one embodiment, the composite conductive agent further includes a flaky conductive agent, wherein the mass ratio of the first granular conductive agent, the fibrous conductive agent and the flaky conductive agent is (0.5-3):(0.2-2):(0.1-2).

[0012] In one embodiment, the particle sizes of the first granular conductive agent and the second granular conductive agent are independently selected from 20 nm to 60 nm;

[0013] And / or, the diameter of the fibrous conductive agent is 4 nm to 200 nm, the length is 1 μm to 200 μm, and the aspect ratio is 5 to 50000;

[0014] And / or, the number of layers of the sheet-like conductive agent is 5 to 15.

[0015] In one embodiment, the first granular conductive agent and the second granular conductive agent are each independently selected from at least one of conductive graphite, conductive carbon black, acetylene black and Ketjen black;

[0016] And / or, the fibrous conductive agent is selected from at least one of carbon nanotubes and carbon nanofibers;

[0017] And / or, the flake-shaped conductive agent is selected from graphene.

[0018] In one embodiment, in the premixed slurry, the mass ratio of the composite conductive agent to the dispersant and the lithium manganese iron phosphate is (0.5-2):(0.03-0.15):(96-97);

[0019] And / or, the dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylate compounds and polyacrylonitrile compounds;

[0020] And / or, in the premixed powder, the mass ratio of the second granular conductive agent to the ternary nickel-cobalt-manganese lithium oxide is 1:97 to 3:96;

[0021] And / or, in the mixed slurry, the mass ratio of the lithium iron manganese phosphate to the ternary lithium nickel cobalt manganese oxide is 1:4 to 9:1.

[0022] In one embodiment, the solid content of the polyvinylidene fluoride glue is 3% to 6%;

[0023] And / or, the solid content of the conductive paste is 4% to 6%;

[0024] And / or, the solid content of the mixed slurry is 80% to 85%;

[0025] And / or, after the viscosity of the mixed slurry is adjusted, the solid content is 65% to 75%, and the viscosity is 5000 mPa·s to 10000 mPa·s.

[0026] In one embodiment, in the step of preparing the mixed slurry, the premixed slurry is added to the premixed powder in batches for mixing.

[0027] The present invention also provides a lithium battery positive electrode slurry prepared by the homogenization method as described above.

[0028] The present invention also provides a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer arranged on the surface of the positive electrode collector, and the positive electrode material layer is made of the lithium battery positive electrode slurry as described above.

[0029] The present invention also provides a lithium battery, which comprises the positive electrode plate as described above.

[0030] The above-mentioned homogenization method first mixes LMFP with a specific amount of a first granular conductive agent and a fibrous conductive agent to obtain a premixed slurry, and then mixes the premixed powder of NCM and a second granular conductive agent with the premixed slurry, effectively constructing a multi-dimensional conductive network combining points and lines on the surface of LMFP, while ensuring that the surface of NCM is coated with the second granular conductive agent. Therefore, it is not only conducive to achieving effective contact between the conductive agent and the active material, but also effectively improves the dispersion uniformity of the particles in the positive electrode slurry, improves the stability of the positive electrode slurry, and further, is conducive to improving the conductivity of the prepared lithium battery, reducing the internal resistance of the battery, and improving the rate performance and cycle performance, and has a wide range of application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is a flow chart of a homogenization method for lithium battery positive electrode slurry in one embodiment of the present invention;

[0033] Figure 2 The figures are test results of the capacity retention rate of lithium battery cells prepared with the positive electrode slurries of Example 1 and Comparative Example 1 of the present invention, wherein (a) is the capacity retention rate of the lithium battery cell prepared with the positive electrode slurry of Example 1, and (b) is the capacity retention rate of the lithium battery cell prepared with the positive electrode slurry of Comparative Example 1;

[0034] Figure 3 The DCR growth rate test result diagram of the lithium battery cells prepared with the positive electrode slurry of Example 1 and Comparative Example 1 of the present invention, wherein (a) is the DCR growth rate of the lithium battery cell prepared with the positive electrode slurry of Example 1, and (b) is the DCR growth rate of the lithium battery cell prepared with the positive electrode slurry of Comparative Example 1. DETAILED DESCRIPTION

[0035] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0037] like Figure 1 As shown, it is a flow chart of a homogenization method of a lithium battery positive electrode slurry in one embodiment of the present invention, and the homogenization method comprises the following steps:

[0038] S1. Mixing a composite conductive agent, a dispersant and a polyvinylidene fluoride glue to obtain a conductive slurry, wherein the composite conductive agent comprises a first granular conductive agent and a fibrous conductive agent, and a mass ratio of the first granular conductive agent to the fibrous conductive agent is 1:4 to 15:1;

[0039] S2, mixing the conductive slurry with lithium iron manganese phosphate to obtain a premixed slurry;

[0040] S3, mixing ternary nickel-cobalt-manganese lithium oxide with a second granular conductive agent to obtain a premixed powder;

[0041] S4, mixing the premixed slurry with the premixed powder to obtain a mixed slurry, adjusting the viscosity of the mixed slurry, and then vacuuming and sieving to obtain a positive electrode slurry for a lithium battery.

[0042] The above-mentioned homogenization method firstly mixes LMFP with a specific amount of a first granular conductive agent and a fibrous conductive agent to obtain a premixed slurry, and then mixes the premixed powder of NCM and the second granular conductive agent with the premixed slurry, effectively constructing a multi-dimensional conductive network combining points and lines on the surface of LMFP, and at the same time, effectively ensuring that the surface of NCM is coated with the second granular conductive agent, effectively avoiding the problem that when LMFP and NCM dry powder are directly mixed in the traditional homogenization method, small particles of LMFP (D 50 0.4μm~1μm) are adsorbed on large particles of NCM (D 50 The surface of the LMFP is 5μm~15μm), which leads to the agglomeration and stratification of the slurry and the poor contact between the conductive agent and NCM. As a result, after the lithium battery is cycled, the electrode expands, resulting in a gap between LMFP and NCM. The LMFP and NCM are easily separated from each other to form an island, which leads to a rapid increase in the internal resistance of the lithium battery and affects the electrochemical performance of the lithium battery.

[0043] Therefore, the present invention not only realizes effective contact between the conductive agent and the active material, but also effectively reduces the sedimentation of large particles of NCM and the agglomeration of small particles of LMFP, effectively improves the dispersion uniformity of particles in the positive electrode slurry, improves the stability of the positive electrode slurry, and further, is conducive to improving the conductivity of the prepared lithium battery, reducing the internal resistance of the battery, and improving the rate performance and cycle performance, and has broad application prospects.

[0044] It should be noted that steps S1 and S2 prepare premixed slurry, and step S3 prepares premixed powder. The present invention has no special requirements for the order of preparing premixed slurry and premixed powder. For example, steps S1 and S2 can be performed first, and then step S3, or step S3 can be performed first, and then steps S1 and S2.

[0045] In one embodiment, the solid content of the polyvinylidene fluoride glue is 3% to 6%.

[0046] Preferably, the solid content of the polyvinylidene fluoride adhesive is 3.5% to 4.5%.

[0047] It should be noted that the polyvinylidene fluoride glue of the present invention is prepared by conventional methods in the art, and the present invention has no special limitation on this. Specifically, polyvinylidene fluoride is added to a solvent, stirred and dispersed, and then defoamed to obtain the polyvinylidene fluoride glue, and the solvent is selected from nitrogen methyl pyrrolidone.

[0048] In order to improve the dispersion uniformity of the composite conductive agent in the conductive paste, the composite conductive agent and the dispersant are preferably added to the polyvinylidene fluoride glue solution, mixed, and stirred for 10 minutes to 30 minutes to obtain the conductive paste.

[0049] Specifically, the solid content of the conductive paste is 4% to 6%.

[0050] At present, the use of a single conductive agent in the positive electrode slurry may lead to problems such as conductive agent agglomeration, low conductive efficiency, and excessive conductive agent addition, thereby reducing the specific energy and specific power of the lithium battery. In severe cases, it may also cause irreversible side reactions inside the lithium battery, reduce the cycle life of the lithium battery, and even bring safety hazards. The present invention effectively forms a point-line combined conductive network on the surface of LMFP by compounding the first granular conductive agent with the fibrous conductive agent, improves the dispersion uniformity of the conductive agent, significantly improves the effective contact between the conductive agent and the active material LMFP, and can give full play to the synergistic coupling effect of the first granular conductive agent and the fibrous conductive agent, improve ionic and electronic conductivity to reduce the internal resistance of the battery cell, and improve the rate and cycle performance.

[0051] In one embodiment, the particle size of the first granular conductive agent is 20 nm to 60 nm, which is beneficial to improving the specific surface area and conductive performance.

[0052] Specifically, the first particulate conductive agent is selected from at least one of conductive graphite, conductive carbon black, acetylene black and Ketjen black.

[0053] In one embodiment, the diameter of the fibrous conductive agent is 4 nm to 200 nm, the length is 1 μm to 200 μm, and the aspect ratio is 5 to 50,000, which is beneficial to improving the carrier migration ability, forming a more complete conductive network, and improving the conductive performance.

[0054] Further preferably, the diameter of the fibrous conductive agent is 4 nm to 15 nm, the length is 20 μm to 200 μm, and the aspect ratio is 4000 to 10000.

[0055] Specifically, the fibrous conductive agent is selected from at least one of carbon nanotubes and carbon nanofibers.

[0056] In order to further improve the stability and conductivity of the multi-dimensional conductive network, the composite conductive agent preferably also includes a flake conductive agent, which is conducive to constructing a point-line-surface combined multi-dimensional conductive network on the surface of the LMFP.

[0057] Specifically, the mass ratio of the first granular conductive agent, the fibrous conductive agent, and the sheet-like conductive agent is (0.5-3):(0.2-2):(0.1-2).

[0058] Preferably, the number of layers of the sheet-like conductive agent is 5 to 15.

[0059] Specifically, the flake-shaped conductive agent is selected from graphene.

[0060] In order to further promote the contact between LMPF and the composite conductive agent, in the premixed slurry, the mass ratio of the composite conductive agent to the dispersant and the lithium manganese iron phosphate is preferably (0.5-2):(0.03-0.15):(96-97).

[0061] In order to further promote the contact between NCM and the second granular conductive agent, in the premixed powder, the mass ratio of the second granular conductive agent to the ternary nickel cobalt manganese oxide is preferably 1:97 to 3:96.

[0062] Specifically, the particle size of the second granular conductive agent is 20 nm to 60 nm.

[0063] Specifically, the second particulate conductive agent is selected from at least one of conductive graphite, conductive carbon black, acetylene black and Ketjen black.

[0064] It should be noted that the first particulate conductive agent and the second particulate conductive agent of the present invention may be of the same type or different particle sizes.

[0065] LMFP(LiMn 1-x Fe x NCM (LiNiPO4) is a material developed on the basis of lithium iron phosphate modification. It has similar properties to lithium iron phosphate and lithium manganese phosphate, and has excellent thermal and chemical stability, so it is safer. Compared with lithium iron phosphate, LMFP has a higher voltage platform, and its electrical conductivity and lithium ion conductivity are improved compared with lithium manganese phosphate. It is a positive electrode material worthy of attention. However, in the positive electrode slurry, the conductivity of single LMFP is poor. NCM (LiNiPO4) is a material developed on the basis of lithium iron phosphate modification. It has excellent thermal and chemical stability, so it is safer. Compared with lithium iron phosphate, LMFP has a higher voltage platform, and its electrical conductivity and lithium ion conductivity are improved compared with lithium manganese phosphate. It is a positive electrode material worthy of attention. However, in the positive electrode slurry, the conductivity of single LMFP is poor. x Co y Mn 1-x-y O2) has the advantages of high energy density, good endurance and good rate performance. However, in the positive electrode slurry, the safety of a single NCM is low and high. The present invention combines the advantages of LMFP and NCM, takes into account high energy density, rate performance, safety and economy, and comprehensively improves the electrochemical performance of the prepared lithium battery. In the mixed slurry, the mass ratio of the lithium manganese iron phosphate to the ternary nickel cobalt manganese oxide is preferably 1:4 to 9:1.

[0066] In order to further improve the dispersion uniformity of particles in the mixed slurry, improve the stability of the positive electrode slurry, and thereby improve the conductivity of the prepared lithium battery, reduce the internal resistance of the battery, and improve the rate performance and cycle performance, in the step of preparing the mixed slurry, it is preferred to add the premixed slurry into the premixed powder in batches for mixing.

[0067] Further preferably, 50% of the premixed slurry is first added to the premixed powder and stirred, and then the remaining 50% of the premixed slurry is added to the premixed powder and stirred.

[0068] Specifically, the solid content of the mixed slurry is 80% to 85%.

[0069] It should be noted that the method for adjusting the viscosity of the mixed slurry in the present invention is an existing method in the art. Specifically, polyvinylidene fluoride glue is added to the mixed slurry, and after stirring and dispersing, it is further added to nitrogen methyl pyrrolidone solvent and stirred and dispersed to obtain a mixed slurry with a specific solid content and viscosity.

[0070] Specifically, after the viscosity of the mixed slurry is adjusted, the solid content thereof is 65% to 75%, and the viscosity is 5000 mPa·s to 10000 mPa·s.

[0071] The present invention also provides a lithium battery positive electrode slurry prepared by the homogenization method as described above.

[0072] The present invention also provides a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer arranged on the surface of the positive electrode collector, and the positive electrode material layer is made of the lithium battery positive electrode slurry as described above.

[0073] The present invention also provides a lithium battery, which includes the positive electrode plate as described above. The lithium battery has excellent electrical conductivity, rate performance and cycle performance, and has broad application prospects.

[0074] Hereinafter, the lithium battery positive electrode slurry and its homogenization method and application will be further described through the following specific examples.

[0075] Example 1

[0076] Add polyvinylidene fluoride adhesive to N-methylpyrrolidone solvent, stir and disperse, remove bubbles after mixing evenly, and form polyvinylidene fluoride glue with a solid content of 4%; add a composite conductive agent and polyvinyl pyrrolidone (PVP) to the polyvinylidene fluoride glue and stir for 2 hours, wherein the composite conductive agent includes conductive carbon black (particle size of 20nm~40nm), carbon nanotubes (tube diameter of 5nm~10nm, length of 50μm~160μm, aspect ratio of 5000~8000) and graphene (number of layers of 8~10), the mass ratio of conductive carbon black, carbon nanotubes and graphene is 0.5:0.2:0.1, and the solid content of the obtained conductive slurry is 6%.

[0077] LMFP was added into the conductive slurry and stirred and dispersed to obtain a premixed slurry, wherein the mass ratio of the composite conductive agent, the dispersant and the LMFP was 1:0.05:96.

[0078] The NCM and the conductive carbon black powder are mixed to obtain a premixed powder, wherein the mass ratio of the NCM to the conductive carbon black is 96:2.

[0079] 50% by weight of the premixed slurry is added to the premixed powder and stirred and dispersed, and the remaining 50% by weight of the premixed slurry is added and continued to be stirred and dispersed to obtain a mixed slurry with a solid content of 85%, wherein the mass ratio of LMFP to NCM is 7:3; polyvinylidene fluoride glue and N-methylpyrrolidone are added to the mixed slurry in sequence and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 70% and the viscosity is 6500mPa·s; the mixed slurry after the viscosity is adjusted is vacuumed, bubbles are removed, and sieved to obtain a positive electrode slurry.

[0080] Example 2

[0081] Add polyvinylidene fluoride adhesive to N-methylpyrrolidone solvent, stir and disperse, remove bubbles after mixing evenly, and form polyvinylidene fluoride glue with a solid content of 4%; add composite conductive agent and PD dispersant to the polyvinylidene fluoride glue and stir for 2 hours, wherein the composite conductive agent includes conductive carbon black (particle size of 40nm~60nm) and carbon nanotubes (tube diameter of 8nm~10nm, length of 80μm~120μm, aspect ratio of 8000~10000), the mass ratio of conductive carbon black to carbon nanotubes is 4:1, and the solid content of the obtained conductive slurry is 6%.

[0082] LMFP was added into the conductive slurry and stirred and dispersed to obtain a premixed slurry, wherein the mass ratio of the composite conductive agent, the dispersant and the LMFP was 1:0.05:96.

[0083] The NCM and the conductive carbon black powder are mixed to obtain a premixed powder, wherein the mass ratio of the NCM to the conductive carbon black is 1.5:96.5.

[0084] The premixed slurry is added to the premixed powder and stirred and dispersed to obtain a mixed slurry with a solid content of 80%, wherein the mass ratio of LMFP to NCM is 1:1; polyvinylidene fluoride glue and N-methylpyrrolidone are added to the mixed slurry in sequence and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 65% and the viscosity is 6000 mPa·s; the mixed slurry after the viscosity is adjusted is vacuumed, bubbles are removed, and sieved to obtain a positive electrode slurry.

[0085] Example 3

[0086] Add polyvinylidene fluoride adhesive to N-methylpyrrolidone solvent, stir and disperse, remove bubbles after mixing evenly, and form polyvinylidene fluoride glue with a solid content of 4%; add composite conductive agent and PVP to the polyvinylidene fluoride glue and stir for 2.5 hours, wherein the composite conductive agent includes conductive graphite (particle size of 40nm~60nm), carbon nanofiber (tube diameter of 10nm~50nm, length of 100μm~120μm, aspect ratio of 2000~10000) and graphene (number of layers of 10~15), the mass ratio of conductive graphite, carbon nanofiber and graphene is 1:0.4:0.1, and the solid content of the obtained conductive slurry is 5.5%.

[0087] LMFP was added into the conductive slurry and stirred and dispersed to obtain a premixed slurry, wherein the mass ratio of the composite conductive agent, the dispersant and the LMFP was 0.5:0.05:97.

[0088] The NCM and the conductive carbon black powder are mixed to obtain a premixed powder, wherein the mass ratio of the NCM to the conductive carbon black is 96:2.

[0089] 50% by weight of the premixed slurry is added to the premixed powder and stirred and dispersed, and the remaining 50% by weight of the premixed slurry is added and continued to be stirred and dispersed to obtain a mixed slurry with a solid content of 85%, wherein the mass ratio of LMFP to NCM is 3:7; polyvinylidene fluoride glue and N-methylpyrrolidone are added to the mixed slurry in sequence and stirred and dispersed, and the solid content of the mixed slurry is adjusted to 70% and the viscosity is 6500mPa·s; the mixed slurry after the viscosity is adjusted is vacuumed, bubbles are removed, and sieved to obtain a positive electrode slurry.

[0090] Comparative Example 1

[0091] The difference between Comparative Example 1 and Example 1 is that a composite conductive agent and PVP are added to the polyvinylidene fluoride glue solution and stirred for 2 hours to obtain a conductive slurry, and LMFP and NCM are added to the conductive slurry and stirred and dispersed to obtain a mixed slurry.

[0092] Comparative Example 2

[0093] The difference between Comparative Example 2 and Example 1 is that in the composite conductive agent used, the mass ratio of conductive carbon black to carbon nanotubes is 1:5.

[0094] Comparative Example 3

[0095] The difference between Comparative Example 3 and Example 1 is that in the composite conductive agent used, the mass ratio of conductive carbon black to carbon nanotubes is 16:1.

[0096] Comparative Example 4

[0097] The difference between Comparative Example 4 and Example 1 is that the composite conductive agent used includes 50 wt % of conductive carbon black and 50 wt % of graphene.

[0098] Comparative Example 5

[0099] The difference between Comparative Example 5 and Example 1 is that, when preparing the conductive paste, carbon nanotubes are used instead of the composite conductive agent.

[0100] Application Examples

[0101] The positive electrode slurries prepared in all the embodiments and comparative examples were subjected to a coating, drying and rolling process to prepare positive electrode sheets, which were matched with graphite negative electrode sheets to prepare lithium battery cells through slitting, winding, drying, liquid injection, and capacity separation processes.

[0102] The viscosity of the positive electrode slurries prepared in all embodiments and comparative examples at the time of discharge and the change of viscosity with time were tested, and the results are shown in Table 1; the resistivity of the positive electrode sheets prepared in all application embodiments and comparative examples was tested, and the lithium battery cells prepared in all application embodiments and comparative examples were subjected to room temperature cycle tests, and the capacity retention rate and DCR growth rate after 500 cycles were calculated, and the test results are shown in Table 2.

[0103] Table 1

[0104]

[0105]

[0106] Table 2

[0107]

[0108] According to the results in Table 1, when the viscosity of the slurry discharge is similar, the change in viscosity over time of the positive electrode slurry of the embodiment of the present invention after discharge is smaller than that of the comparative example, and the stability is higher. The capacity retention rate results of the battery cells prepared by using Example 1 and Comparative Example 1 are as follows: Figure 2 As shown in Table 2, it can be seen that the positive electrode sheet prepared by the positive electrode slurry of the embodiment of the present invention has a significantly lower resistivity, while the positive electrode sheet prepared by the positive electrode slurry of the comparative example has a higher resistivity; the capacity retention rate results of the battery cells prepared by using Example 1 and Comparative Example 1 are as follows: Figure 3 As shown, combined with the results in Table 2, it can be seen that after 500 cycles, the battery cell prepared by the application embodiment of the present invention has a high capacity retention rate, a long cycle life, and a small DCR growth rate, and the cycle performance of the battery cell prepared by the application embodiment is significantly better than that of the battery cell prepared by the application comparison example. Therefore, the homogenization method of the present invention effectively improves the stability of the positive electrode slurry, thereby improving the conductivity of the prepared lithium battery, reducing the internal resistance of the battery, and improving the rate performance and cycle performance, and has a wide range of application prospects.

[0109] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0110] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for homogenizing a lithium battery positive electrode slurry, characterized in that: The homogenization method comprises the following steps: Mixing a composite conductive agent, a dispersant and a polyvinylidene fluoride glue to obtain a conductive slurry, wherein the composite conductive agent includes a first granular conductive agent and a fibrous conductive agent, and the mass ratio of the first granular conductive agent to the fibrous conductive agent is 1:4 to 15:1; Mixing the conductive slurry with lithium iron manganese phosphate to obtain a premixed slurry; Mixing ternary nickel-cobalt-manganese lithium oxide with a second granular conductive agent to obtain a premixed powder; The premixed slurry is mixed with the premixed powder to obtain a mixed slurry. After the viscosity of the mixed slurry is adjusted, vacuuming and sieving are performed to obtain a positive electrode slurry for a lithium battery.

2. The method for homogenizing a lithium battery positive electrode slurry according to claim 1, characterized in that: The composite conductive agent also includes a flake conductive agent, wherein the mass ratio of the first granular conductive agent, the fibrous conductive agent and the flake conductive agent is (0.5-3):(0.2-2):(0.1-2).

3. The method for homogenizing a lithium battery positive electrode slurry according to claim 2, characterized in that: The particle sizes of the first granular conductive agent and the second granular conductive agent are independently selected from 20 nm to 60 nm; And / or, the diameter of the fibrous conductive agent is 4 nm to 200 nm, the length is 1 μm to 200 μm, and the aspect ratio is 5 to 50000; And / or, the number of layers of the sheet-like conductive agent is 5 to 15.

4. The method for homogenizing a lithium battery positive electrode slurry according to claim 2, characterized in that: The first particulate conductive agent and the second particulate conductive agent are each independently selected from at least one of conductive graphite, conductive carbon black, acetylene black and Ketjen black; And / or, the fibrous conductive agent is selected from at least one of carbon nanotubes and carbon nanofibers; And / or, the flake-shaped conductive agent is selected from graphene.

5. The method for homogenizing a lithium battery positive electrode slurry according to claim 1, characterized in that: In the premixed slurry, the mass ratio of the composite conductive agent to the dispersant and the lithium manganese iron phosphate is (0.5-2):(0.03-0.15):(96-97); And / or, the dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylate compounds and polyacrylonitrile compounds; And / or, in the premixed powder, the mass ratio of the second granular conductive agent to the ternary nickel-cobalt-manganese lithium oxide is 1:97 to 3:96; And / or, in the mixed slurry, the mass ratio of the lithium iron manganese phosphate to the ternary lithium nickel cobalt manganese oxide is 1:4 to 9:

1.

6. The method for homogenizing a lithium battery positive electrode slurry according to claim 1, characterized in that: The solid content of the polyvinylidene fluoride glue is 3% to 6%; And / or, the solid content of the conductive paste is 4% to 6%; And / or, the solid content of the mixed slurry is 80% to 85%; And / or, after the viscosity of the mixed slurry is adjusted, the solid content is 65% to 75%, and the viscosity is 5000 mPa·s to 10000 mPa·s.

7. The method for homogenizing a lithium battery positive electrode slurry according to claim 1, characterized in that: In the step of preparing the mixed slurry, the premixed slurry is added to the premixed powder in batches for mixing.

8. A positive electrode slurry for a lithium battery prepared by the homogenization method according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode material layer arranged on the surface of the positive electrode current collector, and the positive electrode material layer is made of the positive electrode slurry of the lithium battery as claimed in claim 8.

10. A lithium battery, characterized in that: The lithium battery comprises the positive electrode sheet as claimed in claim 9.